Vital Autofluorescence: Application to the Study of Plant Living Cells. (10th September 2012) - Roshchina, Victoria V.
Abstract : The application of various microscopy methods such as luminescence microscopy, microspectrofluorimetry and laser-scanning confocal microscopy has been considered as an approach to study the autofluorescence of plant living cells—from cell diagnostics up to modelling the cell-cell contacts and cell interactions with fluorescent biologically active substances. It bases on the direct observations of secretions released from allelopathic and medicinal species and the cell-donor interactions with cell-acceptors as biosensors (unicellular plant generative and vegetative microspores). Special attention was paid to the interactions with pigmented and fluorescing components of the secretions released by the cells-donors from plant species. Colored components of secretions are considered as histochemical dyes for the analysis of cellular mechanisms at the cell-cell contacts and modelling of cell-cell interactions. The fluorescence of plant biosensors was also recommended for the testing of natural plant excretions as medical drugs.